Setting up and running a therapy business : essential questions and answers - Rye, James (Counselor) (London : Routledge, 2021)
Setting Up and Running a Therapy Businessprovides a succinct, practical, and accessible guidefor counsellors starting out in private practice as well asfor more experienced practitioners who would like advice on how to continue to attract a larger clientele. This second edition has been restructured to bring all the marketing chapters together to help counsellors understand a variety of ways of helping their business grow, and includes new material on using social media. Through the inclusion of topics such assetting up a website, choosing an ideal workplace, marketing, meeting data storage standards (including new material on GDPR),and methods of accepting payments, the author offers his expertise and guidance to help practitioners make wise, workable decisions based on a thorough understanding of the stakes as well as the viable options. As a book that bridges the gap between being a good counsellor and running a successful counselling business, it is a comprehensive read not only for counsellors who are just starting in private practice, but also for senior practitioners seeking a fresh perspective on their business.
Part I: Starting Up; 1. Why should I consider private practice?; 2. What qualifications, experience, and qualities do I need to start a private practice?; 3. What things must I do if I go self-employed?; 4. What should I consider if planning to work from home?; 5. What should I consider if planning to hire a room?; 6. What insurance do I need as a private practitioner?; Part II: Money Issues; 7. How much should I charge?; 8. How much can I expect to earn?; 9. How can I accept payment?; 10. Should I give a first session for free?; 11. Should I charge for sessions when a client doesn't turn up or cancels with short notice?; 12. What are business expenses, and why do I need to bother about them?; Part III: Helping My Business Grow; 13. What are your tips for marketing my business? (1); 14. What are your tips for marketing my business? (2); 15. How can I use social media? By Laura Harley; 16. How can I get a website?; 17. What else can I build for longer-term growth?; 18. How can I increase the chances of an inquiry becoming a client?; 19. How can I increase access to my services?; 20. What about working for agencies?; Part IV: Other Practical Issues; 21. What can I do to increase my personal safety when working alone?; 22. Do I need to give clients a written contract?; 23. If I issue a written contract, what might it include?; 24. What do I need to do about GDPR?; 25. How could I introduce a written contract?; 26. How can I store my notes? 27. Do I need to register with the Information Commission?; 28. Can I work with clients in their own homes?; 29. Will I have to work evening and weekends?; 30. What should I do if I bump into my clients in my locality?; 31. What is a professional will and do I need one?; Part V: Miscellany; 32. What are outcome measures and should I use them?; 33. What is the difference between a sole trader and a limited company?
Previous edition: London: Karnac Books Ltd., 2017.
OCLC-licensed vendor bibliographic record.
Keywords: Counseling -- Vocational guidance; PSYCHOLOGY / General; PSYCHOLOGY / Mental Health